Central Sympathetic Activation and Arrhythmogenesis during Acute Myocardial Infarction: Modulating Effects of Endothelin-B Receptors - Kolettis, Theofilos M.; Kontonika, Marianthi; Barka, Eleonora; Daskalopoulos, Evangelos P.; Baltogiannis, Giannis G.; Tourmousoglou, Christos; Papalois, Apostolos; Kyriakides, Zenon S. (Frontiers in Cardiovascular Medicine, 2015)
Sympathetic activation during acute myocardial infarction is an important arrhythmogenic mechanism, but the role of central autonomic inputs and their modulating factors remain unclear. Using the in vivo rat-model, we examined the effects of clonidine, a centrally-acting sympatholytic agent, in the presence or absence of myocardial endothelin-B (ETB) receptors. We studied wild-type (n=20) and ETB-deficient rats (n=20) after permanent coronary ligation, with or without pretreatment with clonidine. Cardiac rhythm was continuously recorded for 24 hours by implantable telemetry devices, coupled by the assessment of autonomic and heart failure indices. Sympathetic activation and arrhythmogenesis were more prominent in ETB-deficient rats during the early phase post-ligation. Clonidine improved these outcomes throughout the observation period in ETB-deficient rats, but only during the delayed phase in wild-type rats. However, this benefit was counterbalanced by atrioventricular conduction abnormalities and by higher incidence of heart failure, the latter particularly evident in ETB-deficient rats. Myocardial ETB-receptors attenuate the arrhythmogenic effects of central sympathetic activation during acute myocardial infarction. ETB-receptor deficiency potentiates the sympatholytic effects of clonidine and aggravates heart failure. The interaction between endothelin and sympathetic responses during myocardial ischemia/infarction and its impact on arrhythmogenesis and left ventricular dysfunction merit further investigation.